XPages portable command guide a compact resource to XPages application development and the XSP language - Donnelly, Martin 1963- (IBM Press, Pearson plc, 2012)
A Practical Primer for XPages Application Development, Debugging, and Performance Using XPages, Lotus® Notes® and Domino® developers can quickly create state-of-the-art web, mobile, and Notes client business applications using standard technologies like HTML, JavaScript, CSS, and XML. Now, there's a perfect portable XPages quick reference for every working developer. Straight from the experts at IBM®, XPages Portable Command Guide offers fast access to working code, tested solutions, expert tips, and example-driven best practices. Drawing on their unsurpassed experience as IBM XPages lead developers and customer consultants, the authors explore many lesser known facets of the XPages runtime, illuminating these capabilities with dozens of examples that solve specific XPages development problems. Using their easy-to-adapt code examples, you can develop XPages solutions with outstanding performance, scalability, flexibility, efficiency, reliability, and value. Covers lots of commands and parameters related to XPages behavior modification through xsp.properties Notes/Domino configuration files XSP Command Manager and OSGi Console The XSP Client-Side JavaScript Object Server Side JavaScript scripting Server Side JavaScript debugging via global functions, simple programming constructs, and logging Instantly access all XPages commands: Use this book as your quick offline solutions resource Logical how-to topic groupings provide one-stop research Compact size makes it easy to carry with you--wherever you go "Create Your Own Journal" section with blank, lined pages makes it easy to personalize this book for your needs "What Do You Want to Do?" chart inside the front cover helps you quickly find specific tasks Designed for all Lotus and Domino developers with at least some XPages experience, XPages Portable Command Guide is the ideal companion and follow-up to Mastering XPages from IBM Press, the world's #1 book on XPages technology.
Includes bibliographical references and index. - Print version record
Keywords: XPages; Internet programming; Application software -- Development; Web site development; Programmation Internet; Logiciels d'application; Développement; Sites Web; Développement; Application software; Development; Engineering & Applied Sciences; Computer Science